Method for improving hardness of corrosion-resistant austenitic stainless steel for post-treatment key equipment

Through comprehensive smelting and processing technology, the hardness and corrosion resistance of austenitic stainless steel are improved, and the problems of insufficient hardness and intergranular corrosion resistance in spent fuel after treatment environment are solved, and high hardness in high temperature nitric acid solution and Low corrosion rate.

CN119287245APending Publication Date: 2025-01-10INST OF METAL RESEARCH - CHINESE ACAD OF SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411363392.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing austenitic stainless steel has insufficient hardness in spent fuel post-treatment environment and cannot meet the requirements of high hardness and excellent intergranular corrosion resistance at the same time, especially in high-temperature nitric acid solutions containing oxidized metal ions and halogen ions. Intergranular corrosion.

Method used

Using a comprehensive process of ultrapure smelting, homogenization treatment, hot forging, hot rolling, solid solution treatment and cold rolling, the hardness of austenitic stainless steel is improved through grain boundary engineering and deformation hardening, and the components are controlled at low content. C, S, P, increase Si and optimize Cr and Ni content to form a dense double-layer passivation film to protect the material.

Benefits of technology

The microhardness is increased to ≥230HV0.2, meeting the hardness requirements of key components. At the same time, no intergranular corrosion occurs in the post-treatment environment of 95℃ and 6mol/L, and the annual corrosion rate is ≤0.30mm/a, which significantly improves the material's Wear resistance and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005065478970000011
    Figure HDA0005065478970000011
Patent Text Reader

Abstract

The invention relates to a method for improving hardness of corrosion-resistant austenitic stainless steel for post-treatment key equipment, belongs to the field of nuclear energy materials and technologies, and solves the key problem that the austenitic stainless steel has excellent intergranular corrosion resistance but insufficient hardness in a nitric acid solution in a spent fuel post-treatment environment. The preparation process of the austenitic stainless steel comprises the steps of burdening, vacuum induction smelting, vacuum consumable arc smelting, hot forging machining, hot rolling machining, solid solution heat treatment and cold rolling machining, after 10-40% of cold deformation machining is adopted for solid solution state steel, the hardness is increased to 230 HV0.2 or above, and the service index requirements of some key components are met; and intergranular corrosion does not occur in a 6mol / L after-treatment environment nitric acid solution at the temperature not higher than 95 DEG C, and the annual corrosion rate after soaking until the corrosion rate is stable is less than or equal to 0.30 mm / a. The method is mainly applied to the field of spent fuel post-treatment and can also be applied to the field of nitric acid chemical industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the hardness of corrosion-resistant austenitic stainless steel used for post-processing key equipment, belonging to the field of nuclear energy materials and technology. Background Art

[0003] Key equipment in post-processing engineering requires materials with excellent resistance to nitric acid corrosion. For example, the design requires that no intergranular corrosion occurs in near-operating medium conditions (such as 95°C, 6mol / L, nitric acid containing oxidizing metal ions and halogen ions) and the annual corrosion rate after immersion until the corrosion rate stabilizes is ≤0.30mm / a (millimeter / year). At the same time, some key components (such as gear transmission pairs, etc.) also need to withstand damage caused by gear rotation. According to the preliminary design, the material hardness must be ≥230HV 0.2 .

[0004] There is often an irreconcilable contradiction between the hardness and corrosion resistance of materials, that is, the corrosion resistance tends to decrease while the hardness increases. For example, in order to ensure excellent intergranular corrosion resistance, steel is often required to have a lower carbon content (such as: C ≤ 0.01wt%), but the reduction in carbon content will lead to a significant reduction in hardness and strength. Currently, the hardness and strength of commercial corrosion-resistant austenitic stainless steel are generally low. For example, the commonly used 316L, 304L, 304ULC and 310L steels, although they have excellent resistance to pure nitric acid corrosion, have a hardness in the solid solution state of only 160 to 180 HV. 0.2 The hardness range cannot meet the design requirements of key components, and intergranular corrosion will occur in high-temperature nitric acid with strong oxidizing ions. Therefore, there is currently no commercial austenitic steel that can simultaneously meet the requirements of transmission components in post-treatment special environment nitric acid.

[0005] Patent CN113061802 uses 0.8-1.4wt% Ti added to steel and a multi-stage aging heat treatment process to improve the strength and hardness of an austenitic stainless steel by precipitation of Ni3Ti precipitates of different sizes. Patent CN112522619 uses a pressurized method to add high-content N during steel smelting, and improves hardness and strength through solid solution strengthening of N and 40-60% cold deformation. The prepared material has excellent corrosion resistance in pure nitric acid, but no corrosion experimental research has been carried out in a special nitric acid solution containing oxidizing metal ions and halogen ions in post-treatment. Summary of the invention

[0006] (I) Purpose of the invention

[0007] The purpose of the present invention is to provide a method for improving the hardness of corrosion-resistant austenitic stainless steel used in key post-processing equipment, so that the intergranular corrosion resistance of the austenitic stainless steel in the post-processing nitric acid solution containing oxidizing ions does not decrease, and at the same time has high hardness and wear resistance. It is intended to be used as a material for key transmission parts in spent fuel post-processing, and solves the key problem that the austenitic stainless steel has excellent intergranular corrosion resistance but insufficient hardness in the nitric acid solution in the spent fuel post-processing environment.

[0008] (II) Technical solutions to be adopted to solve the problem:

[0009] A method for improving the hardness of corrosion-resistant austenitic stainless steel for post-processing key equipment, the method comprising the following steps:

[0010] (1) Ultra-pure smelting: The alloy is ultra-purely smelted to prepare ingots using a dual process of vacuum induction melting and vacuum consumable arc melting;

[0011] (2) Homogenization treatment: After removing the ingot riser and surface oxide scale, homogenization treatment is carried out. The homogenization holding temperature is 1100-1250°C and the holding time is ≥20h;

[0012] (3) Hot forging: The ingot after homogenization treatment is subjected to hot forging. The holding temperature before forging is 1100-1250°C and the holding time is ≥2h; the forging temperature is 850°C-1250°C, the forging ratio is ≥5:1, and the ingot is air-cooled to room temperature after forging;

[0013] (4) Hot rolling: The forging blank obtained after hot forging is hot rolled at a rolling temperature of 850°C to 1250°C, the reduction of each rolling pass is controlled to be 5% to 10%, and the total reduction is controlled to be 20% to 90%. After rolling, the blank is air-cooled to room temperature.

[0014] (5) Solution treatment: The plate obtained after hot rolling is subjected to solution treatment at a solution temperature of 1000-1250°C, a holding time of 0.1-5 hours, and then rapid cooling, with a cooling rate of ≥50°C / min in the range of 500-800°C;

[0015] (6) Cold rolling: Cold rolling deformation processing is carried out at room temperature. Low-energy grain boundaries are introduced through grain boundary engineering to control the total deformation within the range of 10-40%.

[0016] The method for improving the hardness of corrosion-resistant austenitic stainless steel for post-processing key equipment is as follows: the composition of the stainless steel is as follows, in weight percentage: 15.0≤Cr≤20.0, 12.0≤Ni≤18.0, 3.0≤Si≤6.0, 0.05≤Mn≤2.0, 0.05≤W+Mo≤2.0, N≤0.20, Nb+V≤0.20, rare earth element RE≤0.05, and the balance is Fe and unavoidable impurity elements, impurity elements: C≤0.010, P≤0.005, S≤0.005, O≤0.005, B≤0.005.

[0017] The method for improving the hardness of corrosion-resistant austenitic stainless steel for post-processing key equipment, microhardness ≥ 230HV 0.2 .

[0018] The method for improving the hardness of corrosion-resistant austenitic stainless steel for post-processing key equipment does not cause intergranular corrosion in a post-processing environment nitric acid solution of 6 mol / L and not higher than 95°C, and the annual corrosion rate after immersion until the corrosion rate stabilizes is ≤0.30 mm / a; and does not cause intergranular corrosion and the annual corrosion rate is ≤0.60 mm / a after corrosion in 14.4 mol / L boiling nitric acid for 240 hours.

[0019] The design idea of ​​the present invention is:

[0020] The Chinese patent application (application number 202411337813.X) proposes a corrosion-resistant austenitic stainless steel for spent fuel reprocessing and a preparation method thereof. The composition of the stainless steel is as follows, by weight percentage: 15.0≤Cr≤20.0, 12.0≤Ni≤18.0, 3.0≤Si≤6.0, 0.05≤Mn≤2.0, 0.05≤W+Mo≤2.0, N≤0.20, Nb+V≤0.20, rare earth element RE≤0.05, the balance is Fe and unavoidable impurity elements, impurity elements: C≤0.010, P≤0.005, S≤0.005, O≤0.005, B≤0.005. The stainless steel preparation method is: vacuum induction melting → vacuum consumable remelting → thermal mechanical processing → solution treatment, which solves the key problem that the existing domestic commercial austenitic stainless steel is prone to intergranular corrosion in the special environment of spent fuel reprocessing nitric acid medium, but its microhardness in the solid solution state is only ~167HV 0.2 The present invention adopts a preparation method that can improve the hardness and wear resistance of austenitic stainless steel with excellent intergranular corrosion resistance in nitric acid solution containing spent fuel radioactive ions. After 10% cold deformation, the microhardness is 235HV 0.2 , meet the service index requirements (microhardness ≥ 230HV 0.2 ); 311HV after 20% cold deformation 0.2, far higher than the service requirements. At the same time, after cold deformation, austenitic stainless steel does not suffer from intergranular corrosion in nitric acid solution at room temperature to 95°C, concentration to 6 mol / L, and post-treatment special environment, and the annual corrosion rate is ≤0.30mm / a after immersion until the corrosion rate stabilizes. It does not suffer from intergranular corrosion and the annual corrosion rate is ≤0.60mm / a after immersion in 14.4 mol / L boiling concentrated nitric acid for 240 hours, meeting the service requirements.

[0021] The advantages and beneficial effects of the present invention are:

[0022] (1) In order to achieve the excellent intergranular corrosion resistance performance requirements, the composition design of the austenitic stainless steel of the present invention is: on the one hand, the elements such as C, S and P in the steel are designed and controlled to be as low as possible, eliminating the main factors of sensitization and intergranular corrosion of conventional austenitic stainless steel; on the other hand, an appropriate amount of Si is added and the Cr and Ni contents are coordinated and optimized to form a dense double-layer passivation film to protect the substrate from corrosion by high-temperature nitric acid and oxidizing ions.

[0023] (2) In order to meet the hardness requirement, the corrosion-resistant austenitic stainless steel of the present invention has the following processing techniques: on the one hand, a small amount of cold rolling processing (deformation amount 10-40%) is adopted to greatly improve the hardness of the material through deformation hardening, thereby meeting the service design requirements and having a simple process; on the other hand, a large number of low-energy grain boundaries are generated through grain boundary engineering to ensure that the corrosion resistance of the material is not reduced, thus breaking the tradition that the corrosion resistance of conventional materials is significantly reduced due to the introduction of a large number of defects such as dislocations during cold processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Low-magnification metallographic photographs of the microstructure of Example 1: (a) solid solution state; (b) 20% cold deformation state.

[0025] Figure 2 High-magnification TEM photos of the microstructure of the material of Example 1: (a) solid solution state; (b) 20% cold deformation.

[0026] Figure 3 SEM photos of the corrosion surface morphology of the material in Example 1: (a) solid solution state; (b) 20% cold deformation state; (immersion corrosion test conditions: boiling, 14.4 mol / L pure nitric acid solution, corrosion time 240 h).

[0027] Figure 4 SEM photos of the corrosion surface morphology of the material in Example 1: (a) solid solution state, corrosion time 5472h; (b) 20% cold deformation, corrosion time 384h; (immersion corrosion test conditions: 95°C, 6mol / L, nitric acid solution containing oxidizing ions).

[0028] Figure 5SEM photos of the corrosion surface morphology of the material in Comparative Example 1: (a) solid solution state, corrosion time 5472h; (b) 20% cold deformation state, corrosion time 240h; (immersion corrosion test conditions: 95°C, 6mol / L, nitric acid solution containing oxidizing ions).

[0029] Figure 6 SEM photos of the corrosion surface morphology of the solid solution material in Comparative Example 2: (a) 95°C, 14.4 mol / L nitric acid, corrosion time 240 h; (b) 95°C, 6 mol / L nitric acid solution containing oxidizing ions, corrosion time 240 h. DETAILED DESCRIPTION

[0030] The following examples will further illustrate the present invention, but are not intended to limit the present invention. The steels in the examples and comparative examples were subjected to purification smelting, hot working, solution heat treatment and cold working with a certain amount of deformation, and then their hardness and corrosion resistance were tested and studied.

[0031] The following is a detailed description in conjunction with the attached tables and drawings, which constitute a part of this application and are used together with the embodiments and comparative examples to illustrate the principles of the present invention.

[0032] Example 1

[0033] In this embodiment, the alloy composition of austenitic stainless steel is, by weight percentage (wt%): Cr: 15.5; Ni: 15.2; Mn: 1.5; Si: 4.1; Mo: 0.2; N: 0.05; Nb: 0.1; RE (lanthanum): 0.01; C: 0.008; O: 0.003; P: 0.005; S: 0.005; B: 0.001; the remainder is iron.

[0034] The preparation process of austenitic stainless steel in this embodiment is: batching → vacuum induction smelting → vacuum consumable arc smelting → hot forging → hot rolling → solution heat treatment → cold rolling. The specific steps are as follows:

[0035] (1) High-purity raw materials are used and prepared according to the proportion of alloy elements. They are purified and smelted in a 200 kg vacuum induction furnace, and then vacuum consumable arc smelting and casting are performed to obtain steel ingots. The surface oxide scale is removed and the ingot riser is cut off.

[0036] (2) The ingot is subjected to long-term homogenization treatment and hot forging in the austenite phase region: the holding temperature is 1250°C for 20 hours; the starting forging temperature is 1200°C, the final forging temperature is 850°C, the forging ratio is about 5:1, and the ingot is air-cooled to room temperature after forging.

[0037] (3) The forging blank after hot forging is hot rolled: the starting rolling temperature is 1200°C, the final rolling temperature is 850°C, the rolling reduction in each pass is controlled to be 10%, the total deformation is controlled to be 50%, and the blank is air-cooled to room temperature after rolling.

[0038] (4) The hot rolled plate is subjected to a solution treatment, the solution heat temperature is 1200°C, the holding time is 2 hours, and the cooling method is water cooling, wherein the cooling rate in the range of 500-800°C is about 110°C / min.

[0039] (5) Cold deformation: The two solution treated plates were subjected to cold rolling deformation, with a reduction of 5% per pass, and the total deformation was controlled to be 10% and 20% respectively.

[0040] (6) Hardness and corrosion resistance tests were conducted on solid solution and cold deformed samples respectively.

[0041] Example 2

[0042] The alloy composition and preparation process of this embodiment are the same as those of embodiment 1, except that the deformation amount of the last cold deformation process is 40%, and then the performance test of the prepared material is carried out.

[0043] Comparative Example 1

[0044] In this comparative example, the alloy composition of the austenitic stainless steel is, by weight percentage (wt%): Cr: 25.1; Ni: 20.9; Mn: 0.24; Si: 0.11; Mo: 0.1; N: 0.55; C: 0.007; O: 0.001; P: 0.006; S: ​​0.008; the balance is iron.

[0045] In this comparative example, except that the N content is increased to 0.55wt%, the other components are basically the same as those of domestic 310L austenitic stainless steel.

[0046] The processing and preparation process of the austenitic stainless steel in this comparative example is as follows: a steel ingot is obtained by vacuum induction smelting and pouring; the obtained steel ingot is forged in the austenite phase region, the initial forging temperature is about 1230°C, the forging ratio is greater than 5:1, and air-cooling is performed to room temperature after forging; the forged steel ingot is hot-rolled, the start rolling temperature is about 1180°C, the reduction amount of each rolling pass is controlled to be 10%, the total reduction amount is controlled to be 60%, and air-cooling is performed to room temperature after hot rolling; the plate is solution-treated after hot rolling, the temperature is kept at 1200°C for 30 minutes, and then water-quenched to room temperature; the plate after solution treatment is cold-rolled with a deformation amount of 20%, and the hardness and corrosion resistance of the solution state and 20% rolled state samples are tested and evaluated.

[0047] Comparative Example 2

[0048] In this comparative example, the alloy composition of the austenitic stainless steel is, by weight percentage (wt%): Cr: 19.9; Ni: 13.8; Si: 1.09; Mn: 1.92; C: 0.004; P: 0.005; S: 0.0031; and the balance is iron.

[0049] The material of this comparative example is a purchased commercial 304ULC austenitic stainless steel solid solution state plate. On this basis, after the plate is subjected to 20% cold deformation rolling, the hardness and corrosion resistance of the solid solution state and 20% rolled state samples are tested and evaluated. As shown in Table 1, the microhardness values ​​HV of the embodiment and the comparative example.

[0050] Table 1 Microhardness of the examples and comparative examples in different states

[0051]

[0052] It can be seen from Table 1 that the solid solution hardness of the austenitic stainless steel in the embodiments of the present invention and the comparative examples is lower than 230HV, which cannot meet the component design requirements. Although the N content in the material of comparative example 1 is relatively high (0.55wt%), its hardness is increased compared with the solid solution material of embodiment 1, but it still does not reach 230HV. After the solid solution material of embodiment 1 is processed by cold deformation, the hardness is greatly improved. After only 10% cold deformation, the hardness reaches 235HV, which meets the design requirements (≥230HV). After 20% cold deformation, the hardness reaches 311HV, which far exceeds the index requirements. The hardness of comparative example 1 is also greatly improved after 20% cold deformation. The solid solution hardness of the material of comparative example 2 is relatively low, and even after 20% cold deformation, the hardness is only 152HV, which cannot meet the requirements.

[0053] As shown in Table 2, the corrosion rates of the embodiment and comparative example materials in different states in different nitric acid corrosion solutions.

[0054] Table 2 Corrosion rates of the examples and comparative examples in different nitric acid solutions

[0055]

[0056] Note: " / " is not tested.

[0057] As can be seen from Table 2, the intergranular corrosion experiment of the material was carried out according to the C method of GB / T4334-2020, that is, 5 cycles of corrosion in boiling (about 123°C) pure nitric acid with a concentration of 14.4mol / L for a total of 240h. The corrosion rates of the solid solution state and 10% and 20% cold-deformed materials in Example 1 were 0.48, 0.46 and 0.47mm / a, respectively. In contrast to conventional austenitic stainless steel, the corrosion rate of the material in Example 1 did not increase significantly after cold deformation, but remained almost unchanged or even slightly decreased. It shows that cold deformation has successfully ensured that the corrosion performance does not decrease while greatly improving the hardness of the material in Example 1. The corrosion rates of the solid solution state and 20% cold-deformed materials in Comparative Example 1 are both low. The experimental results of keeping the nitric acid concentration at 14.4mol / L unchanged, but reducing the nitric acid temperature to 95°C, and immersion corrosion for 240h show that the corrosion rates of all examples and comparative examples are greatly reduced, meeting the design index ≤0.3mm / a. The results of the immersion corrosion test after maintaining the nitric acid temperature at 95°C, further reducing the concentration to 6 mol / L, and adding oxidizing ions show that the corrosion rate of all materials has changed, and all corrosion samples have entered the stable period of corrosion rate. Among them, the corrosion rate of the solid solution material in Example 1 after immersion for 5472 hours is 0.25 mm / a, and the corrosion rate of the 20% cold-deformed material after 384 hours is 0.22 mm / a, both of which meet the design requirements. The material of Comparative Example 1, regardless of the solid solution state or the 20% cold-deformed state, has a low corrosion rate in pure nitric acid, but the corrosion rate in the post-treatment nitric acid with the addition of oxidizing ions increases significantly, reaching the range of 0.60-0.70 mm / a, which has exceeded the design indicator of 0.3 mm / a. The corrosion rate of the 304ULC material in Comparative Example 2 is 0.27 mm / a, which is lower than 0.3 mm / a.

[0058] Figure 1 The following are low-magnification metallographic photographs of the microstructure of the sample in the solid solution state and 20% cold deformation state according to Example 1 of the present invention. Figure 1 a It can be seen that the structure of the solid solution sample is full austenite. After 20% cold deformation, the structure is still full austenite ( Figure 1 b), no phase transformation occurs, but the grain size is refined.

[0059] Figure 2 This is a high-magnification TEM photograph of Example 1. Figure 2 It can be seen from a that the grain boundary of the solid solution material is very pure, without precipitation phase and inclusions, and the dislocation density is low. Figure 2 b It can be seen that after 20% cold deformation, the dislocation density increases significantly. The refinement of grain size and the significant increase in dislocation density are the main reasons for the increase in hardness of the material in Example 1.

[0060] Figure 3This is a SEM photo of the surface morphology of the material in Example 1 after being corroded in boiling (about 123°C) 14.4 mol / L nitric acid for 240 hours. Figure 3 It can be seen that regardless of the solid solution state ( Figure 3 a) or 20% cold deformation ( Figure 3 b), no intergranular corrosion and pitting corrosion occurred in the materials, indicating that the cold-deformed example materials still have excellent intergranular corrosion resistance in boiling concentrated nitric acid.

[0061] Figure 4 This is a SEM photo of the corrosion surface morphology of the material in Example 1 in 95°C, 6 mol / L nitric acid containing oxidizing ions. Figure 4 It can be seen from a that the surface of the solid solution material in Example 1 is a typical uniform corrosion morphology, and no intergranular corrosion and pitting corrosion are observed. Figure 4 As can be seen from b, after 384 hours of corrosion of the material with 20% cold deformation, scratches left during sample preparation before corrosion can still be observed on the material surface, indicating that intergranular corrosion and pitting corrosion have not occurred. Combined with the hardness data in Table 1 and the corrosion rate data in Table 2, it can be seen that the cold-deformed Example 1 material has a higher hardness and still has excellent intergranular corrosion resistance in the post-treatment near-working condition special nitric acid corrosion medium.

[0062] Figure 5 This is a SEM photo of the corrosion surface morphology of the material in comparative example 1 in 95°C, 6 mol / L, nitric acid containing oxidizing ions for post-treatment. Figure 5 It can be seen from a that after 5472h of corrosion, the solid solution material shows severe intergranular corrosion morphology. Figure 5 b It can be seen that the material after 240 hours of corrosion and 20% cold deformation has a high hardness (344 HV), but serious intergranular corrosion occurs. Therefore, the material of Comparative Example 1 is not suitable for use in a post-treatment environment containing oxidizing ions such as nitric acid.

[0063] Figure 6 The following are SEM photos of the corrosion surface morphology of the solid solution material in comparative example 2 under different full immersion corrosion conditions. Figure 6 It can be seen from a that after corrosion for 240h in 95℃ and 14.4mol / L nitric acid, although the 304ULC material has a low corrosion rate (0.02mm / a), the corrosion morphology shows slight signs of intergranular corrosion. Figure 6 b It can be seen that after being corroded in a nitric acid solution containing oxidizing ions at 95°C and 6 mol / L for 240 hours, the 304ULC material exhibits the morphology of intergranular corrosion, which indicates that the 304ULC material is also not suitable for use in a high-temperature nitric acid environment containing oxidizing ions in post-treatment.

[0064] The results of the embodiments and comparative examples show that the corrosion-resistant austenitic stainless steel for spent fuel reprocessing of a specific composition has a low hardness in the solid solution state and is difficult to meet the service index requirements of some key components. The hardness of the solid solution steel is increased to 230HV after 10-40% cold deformation. 0.2 The above meets the service index requirements of certain key components, and no intergranular corrosion occurs in a post-processing environment nitric acid solution not higher than 95°C and 6mol / L, and the annual corrosion rate after immersion until the corrosion rate stabilizes is ≤0.30mm / a. The present invention is mainly used for certain key components (such as: spent fuel dissolver rotor, gear transmission pair, etc.) in the field of spent fuel post-processing and nitric acid chemical industry, and can withstand the damage caused by the rotation of these key components.

Claims

1. A method for improving the hardness of corrosion-resistant austenitic stainless steel for post-processing key equipment, characterized in that: The method comprises the following steps: (1) Ultra-pure smelting: The alloy is ultra-purely smelted to prepare ingots using a dual process of vacuum induction melting and vacuum consumable arc melting; (2) Homogenization treatment: After removing the ingot riser and surface oxide scale, homogenization treatment is carried out. The homogenization holding temperature is 1100-1250°C and the holding time is ≥20h; (3) Hot forging: The ingot after homogenization treatment is subjected to hot forging. The holding temperature before forging is 1100-1250°C and the holding time is ≥2h; the forging temperature is 850°C-1250°C, the forging ratio is ≥5:1, and the ingot is air-cooled to room temperature after forging; (4) Hot rolling: The forging blank obtained after hot forging is hot rolled at a rolling temperature of 850°C to 1250°C, the reduction of each rolling pass is controlled to be 5% to 10%, and the total reduction is controlled to be 20% to 90%. After rolling, the blank is air-cooled to room temperature. (5) Solution treatment: The plate obtained after hot rolling is subjected to solution treatment at a solution temperature of 1000-1250°C, a holding time of 0.1-5 hours, and then rapid cooling, with a cooling rate of ≥50°C / min in the range of 500-800°C; (6) Cold rolling: Cold rolling deformation processing is carried out at room temperature. Low-energy grain boundaries are introduced through grain boundary engineering to control the total deformation within the range of 10-40%.

2. The method for improving the hardness of corrosion-resistant austenitic stainless steel for post-processing key equipment according to claim 1, characterized in that: In terms of weight percentage, the composition of stainless steel is as follows: 15.0≤Cr≤20.0, 12.0≤Ni≤18.0, 3.0≤Si≤6.0, 0.05≤Mn≤2.0, 0.05≤W+Mo≤2.0, N≤0.20, Nb+V≤0.20, rare earth element RE≤0.05, the balance is Fe and unavoidable impurity elements, impurity elements: C≤0.010, P≤0.005, S≤0.005, O≤0.005, B≤0.

005.

3. The method for improving the hardness of corrosion-resistant austenitic stainless steel for post-processing key equipment according to claim 1 or 2, characterized in that: Microhardness ≥230HV 0.2 .

4. The method for improving the hardness of corrosion-resistant austenitic stainless steel for post-processing key equipment according to claim 3, characterized in that: In the post-treatment environment nitric acid solution at a temperature not higher than 95°C and 6 mol / L, no intergranular corrosion occurs, and the annual corrosion rate is ≤0.30 mm / a after immersion until the corrosion rate stabilizes; in 14.4 mol / L boiling nitric acid, no intergranular corrosion occurs for 240 hours and the annual corrosion rate is ≤0.60 mm / a.